MUSIC IN HUMAN LIFE: मानव जीवन में संगीत की उपादेयता - Arande, Kishore (International Journal of Research -GRANTHAALAYAH, 2015)
Music is very important in all the fine arts. Through its study and practice, man achieves both cosmic and supernatural happiness. Human life is full of music. Man is a pious creature of knowledge. Therefore, he gets special pleasure from music. Human life is always inspired by music. Human life is the center of conflicting emotions like rise and fall, joyous controversy and raga malice. Where on one side the complex problems of life keep worrying man. On the other hand, music keeps addressing all the worries of man. समस्त ललित कलाओं में संगीत का स्थान अत्यन्त महत्वपूर्ण है। इसके अध्ययन और अभ्यास से मनुष्य लौकिक तथा अलौकिक दोनों सुख प्राप्त करता है। मानव जीवन संगीत से ओत-प्रोत है। मनुष्य ज्ञान शील प्राणी है। अतः उसे संगीत से विशेष आनन्द प्राप्त होता है। मानव जीवन सदा संगीत से अनुप्राणित होता रहता है। मानव जीवन नाना प्रकार के उत्थान-पतन, हर्ष विवाद तथा राग द्वेष आदि द्वन्द्वात्मक भावों का केन्द्र होता है। जहाँ एक ओर जीवन की जटिल समस्यायें मनुष्य को चिन्तित करती रहती है। वहाँ दूसरी ओर संगीत मनुष्य की सारी चिन्ताओं का निराकरण करता रहता है।